2009
DOI: 10.1007/s12666-009-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

Detonation sprayed WC-Co coatings: unique aspects of their structure and mechanical behaviour

Abstract: Tungsten Carbide-Cobalt (WC-Co) Cermets are known for their excellent wear resistance. Conventionally, WC-Co cermets are produced by liquid phase sintering and such a process results in optimum combination and distribution of WC and Co phases and thus a good combination of hardness and toughness. In contrast to using bulk WC-Co, there are many applications wherein a thick coating of WC-Co over the surface of the engineering component (usually made from steel) represents a cost-effective option. Numerous therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, by observing the cutting surface through scanning electron microscope, we found that not all of the experimental results showed the characteristic that the material is cut erosion [26] . The deformation mechanism is considered the effect of plastic deformation and work hardening, so it is more close to the real situation of the erosion process and is often used to deal with the erosion process that have corner, deep cavity, complex shape and special position [27,28] . Finite element method (FEM)is also a method used to simulate particle erosion, especially analyzing the stress and strain distribution in the erosion process which is more effective.…”
Section: Simulation Of the Jet Erosion Workpiecementioning
confidence: 99%
“…However, by observing the cutting surface through scanning electron microscope, we found that not all of the experimental results showed the characteristic that the material is cut erosion [26] . The deformation mechanism is considered the effect of plastic deformation and work hardening, so it is more close to the real situation of the erosion process and is often used to deal with the erosion process that have corner, deep cavity, complex shape and special position [27,28] . Finite element method (FEM)is also a method used to simulate particle erosion, especially analyzing the stress and strain distribution in the erosion process which is more effective.…”
Section: Simulation Of the Jet Erosion Workpiecementioning
confidence: 99%